(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction:Right iliac fossa pathologies are one of the common reasons for right iliac fossa pain & patient presentation to the Emergency department. It may be related to either benign or malignant diseases. Radiological imaging plays a pivotal role in the differential diagnosis among these diseases. Lymphatic involvement of diseases helps us to learn about the nature of the disease and predict the way of progression, hence awareness with the normal lymph node radiological appearance and its suspicious criteria by radiologists is a crucial information for treatment preparation and execution.AIMS AND OBJECTIVES:To describe key imaging findings of various right iliac fossa pathologies.To assess the role of characteristics of lymph nodes in various right iliac fossa pathologies.METHODOLOGY:A total of 50 cases clinically suspected & diagnosed of having right iliac fossa pathology by CECT imaging of abdomen, at the department of Radiodiagnosis, AMC MET Medical college, Maninagar, Ahmedabad were included in this study.CECT was carried out on PHILIPS MX 16 slice CT machine after giving oral, rectal & iv contrast and axial, sagittal and coronal images were obtained.RESULTS:In our study, most common pathology found was acute appendicitis (16/50), followed by ileocaecal tuberculosis (12/50) and non-tuberculous infectious enterocolitis (11/50). The other pathologies encountered were epiploic appendagitis (3/50), caecal malignancy (2/50), diverticulitis (2/50), Crohn’s disease (2/50) and lymphoma (1/50).Discussion & CONCLUSION:CE CT images of abdomen are very helpful in diagnosis of various right iliac fossa pathologies. Demonstration of lymph nodal patterns of enhancement and their characteristics can further help in narrowing the diagnosis of right iliac fossa pathologies.